2007
DOI: 10.1007/s10549-007-9717-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the H2AFX promoter region are associated with risk of sporadic breast cancer in non-Hispanic white women aged ≤55 years

Abstract: The histone protein family member X (H2AFX) is important in maintaining chromatin structure and genetic stability. Genetic variants in H2AFX may alter protein functions and thus cancer risk. In this case-control study, we genotyped four common single nucleotide polymorphisms (i.e., −1654A > G [rs643788], −1420G > A [rs8551], and −1187T > C [rs7759] in the H2AFX promoter region and 1057C > T [rs7350] in the 3′ untranslated region (UTR)) in 467 patients with sporadic breast cancer and 488 cancer-free controls. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
(40 reference statements)
3
22
0
Order By: Relevance
“…It is known that the promoter and 3 0 -UTR regions of a gene have functions in regulating transcription, messenger RNA (mRNA) stability, and gene production [15] and that single-nucleotide polymorphisms (SNPs) are the common genetic variants in these core and proximal promoter regions [16], and thus searching for functional variants in the promoter and 3 0 -UTR regions or regulatory regions of the gene [17][18][19] becomes important. Recently, two molecular epidemiology studies demonstrated that H2AFX promoter polymorphisms may alter susceptibility to cancers, including non-Hodgkin lymphoma [20] and breast cancer [21]. These findings provide support for the hypothesis that SNPs in the H2AFX promoter region are biologically important.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…It is known that the promoter and 3 0 -UTR regions of a gene have functions in regulating transcription, messenger RNA (mRNA) stability, and gene production [15] and that single-nucleotide polymorphisms (SNPs) are the common genetic variants in these core and proximal promoter regions [16], and thus searching for functional variants in the promoter and 3 0 -UTR regions or regulatory regions of the gene [17][18][19] becomes important. Recently, two molecular epidemiology studies demonstrated that H2AFX promoter polymorphisms may alter susceptibility to cancers, including non-Hodgkin lymphoma [20] and breast cancer [21]. These findings provide support for the hypothesis that SNPs in the H2AFX promoter region are biologically important.…”
Section: Introductionmentioning
confidence: 70%
“…The homozygous AA genotype of rs2509049 upstream of the H2AFX start codon was observed to be strongly associated with protection against NHL, this being the first study to establish a correlation between an H2AFX gene polymorphism and risk of human cancer. Another recent study [21] found that three common SNPs (rs643788, rs8511, and rs7759) in the H2AFX promoter were associated with increased risk of breast cancer in non-Hispanic White women aged B55 years. However, no associations were observed for rs643788, rs8511, and rs7350 in a bladder cancer study [26].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The rs7759 A > G is located at the promoter region of H2AX. Three common tagging SNPs (including rs7759 A > G) in the H2AX promoter region were previously investigated and reported to contribute to the risk of sporadic breast cancer in young non-Hispanic white women, and may regulate the gene expression [27]. In previous studies, the polymorphisms nearby the upstream of H2AX gene were found to regulate the expression of H2AX, modify DNA repair pathway, and influence genetic susceptibility to some diseases by contributing to the maintenance of genome stability [28][29][30].…”
Section: Discussionmentioning
confidence: 99%